The second masking - Mwamba, Corey (Jazz Research Journal, 2020)
This article is a condensed summary of the author’s primary research. Using music, prose, and free verse, I seek to highlight the issues that work revealed within jazz and improvised music studies, and studies into vibraphone practice; briefly show the practical-philosophical roots of my methodology in the research; and present the practice-led roots of my current philosophy of the vibraphone.